A LICHNEROWICZ-TYPE RESULT ON A SEVEN-DIMENSIONAL QUATERNIONIC CONTACT MANIFOLD (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2013)
In this paper we establish an analogue of the classical Lichnerowicz' theorem giving a sharp lower bound of the first non-zero eigenvalue of the sub-Laplacian on a compact seven-dimensional quaternionic contact manifold, assuming a lower bound of the qc-Ricci tensor, torsion tensor and its distinguished covariant derivatives.